Chemisorption of CO2 by chitosan oligosaccharide/DMSO: organic carbamato–carbonato bond formation. Issue 18 (30th August 2017) - Qaroush, Abdussalam K.; Assaf, Khaleel I.; Bardaweel, Sanaa K.; Al-Khateeb, Ala'a; Alsoubani, Fatima; Al-Ramahi, Esraa; Masri, Mahmoud; Brück, Thomas; Troll, Carsten; Rieger, Bernhard; Eftaiha, Ala'a F.
Abstract : A novel oligochitosan/DMSO system as a green sorbent for CO2 capturing. Abstract : A newly formed bond of organic carbamato–carbonato emerged upon bubbling CO2 in a low molecular weight chitosan hydrochloride oligosaccharide CS·HCl/DMSO binary mixture. The aforementioned bond was detected and confirmed using attenuated total reflectance-Fourier transform Infrared (ATR-FTIR) spectroscopy, with two prominent peaks at 1551 cm −1 and 1709 cm −1 corresponding to ionic organic alkylcarbonate (RCO3 − ) and carbamate (RNH–CO2 − NH3 + –R), respectively. 1 H–, 13 C–, and 1 H– 15 N heteronuclear single quantum coherence (HSQC) NMR experiments were also employed. According to 13 C NMR, two newly emerged peaks at 157.4 ppm and 161.5 ppm attributed for the carbonyl carbon within the sequestered species RCO3 − and RNH–CO2 − NH3 + –R, respectively. Upon CO2 bubbling, cross peaks obtained from 1 H– 15 N HSQC at 84.7 and 6.8 ppm correlated to the ammonium counterpart chemical shift bound to the proton resonances. Volumetric uptake of CO2 was measured using an ATR-FTIR autoclave equipped with a silicon probe. The equilibrium sorption capacity was 0.6 and 0.2 bars through the formation of RCO3 − and RNH–CO2 − NH3 + –R, respectively. Moreover, physisorption by the dried DMSO contributed to additional 0.4 bars. Density functional theory (DFT) calculations supported the occurrence of the suggested dual mechanisms and confirmed the formation of carbonate atC-6 of the glucosamine co-monomer. Moreover, CS·HCl/DMSO showed a slight impact on cell proliferation after 48 hours; this was a clear evidence of its non-toxicity. The biodegradation test revealed that a degradation of about 80% of CS·HCl/DMSO was achieved after 33 days; these results indicated that this method is suitable for green industry. CS·HCl/DMSO showed modest activities against Staphylococcus aureus and Escherichia coli . In addition, CS·HCl/DMSO demonstrated a significant antifungal activity against Aspergillus flavus in comparison with Fluconazole.